THE CRITERIA FOR DETERMINING STAGES OF DEVELOPMENT OF ENGLISH TEACHING METHODS IN BUKOVYNA (LATE XIX - EARLY XX CENTURIES) - Oksana Tumak (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2016)
The article is devoted to the criteria for the determining main stages of the development of teaching English methods in Bukovyna in the late XIX - early XX century. To achieve this goal the author refers to the works of scientists-educators who were engaged in the research of the issues of the periodization of the educational thought in Ukraine. The definition of "stage" has been given and the approaches to understanding its importance have been highlighted. The classification of different types of the existing periodizations in pedagogy has been considered; its basic components have been revealed. The development of the criteria for the creation of the periodization was made possible due to the study of the works of scientists-methodologists who investigated methods of teaching foreign languages in a historical context. The author offers two major criteria which served as the basis for separating periods of the development of English teaching methods in Bukovyna in the late XIX - early XX century: 1) historical-social and educational-managing preconditions; 2) qualitative changes in the English teaching methods which took place in Bukovyna in the chosen chronological scope. As a result of the research there were defined three stages: I - (1872 - 1890) the origin of the English teaching methods, II - (1890 - 1908) the formation of English teaching methods, III - (1908 - 1918) the further development of English teaching methods in Bukovyna.